Mister Exam

Other calculators

-15-3*(x-2)=18+x equation

The teacher will be very surprised to see your correct solution 😉

v

Numerical solution:

Do search numerical solution at [, ]

The solution

You have entered [src]
-15 - 3*(x - 2) = 18 + x
3(x2)15=x+18- 3 \left(x - 2\right) - 15 = x + 18
Detail solution
Given the linear equation:
-15-3*(x-2) = 18+x

Expand brackets in the left part
-15-3*x+3*2 = 18+x

Looking for similar summands in the left part:
-9 - 3*x = 18+x

Move free summands (without x)
from left part to right part, we given:
3x=x+27- 3 x = x + 27
Move the summands with the unknown x
from the right part to the left part:
(4)x=27\left(-4\right) x = 27
Divide both parts of the equation by -4
x = 27 / (-4)

We get the answer: x = -27/4
The graph
02-16-14-12-10-8-6-4-2-5050
Rapid solution [src]
x1 = -27/4
x1=274x_{1} = - \frac{27}{4}
x1 = -27/4
Sum and product of roots [src]
sum
-27/4
274- \frac{27}{4}
=
-27/4
274- \frac{27}{4}
product
-27/4
274- \frac{27}{4}
=
-27/4
274- \frac{27}{4}
-27/4
Numerical answer [src]
x1 = -6.75
x1 = -6.75